A gut-vascular barrier controls the systemic dissemination of bacteria - Spadoni, Ilaria; Zagato, Elena; Bertocchi, Alice; Paolinelli, Roberta; Hot, Edina; Di Sabatino, Antonio; Caprioli, Flavio; Bottiglieri, Luca; Oldani, Amanda; Viale, Giuseppe; Penna, Giuseppe; Dejana, Elisabetta; et al. (Science (American Association for the Advancement of Science), 2015)
In healthy individuals, the intestinal microbiota cannot access the liver, spleen, or other peripheral tissues. Some pathogenic bacteria can reach these sites, however, and can induce a systemic immune response. How such compartmentalization is achieved is unknown. We identify a gut-vascular barrier (GVB) in mice and humans that controls the translocation of antigens into the blood stream and prohibits entry of the microbiota. Salmonella typhimurium can penetrate the GVB in a manner dependent on its pathogenicity island (Spi) 2-encoded type III secretion system and on decreased β-catenin-dependent signaling in gut endothelial cells. The GVB is modified in celiac disease patients with elevated serum transaminases, which indicates that GVB dismantling may be responsible for liver damage in these patients. Understanding the GVB may provide new insights into the regulation of the gut-liver axis.